Imprecision Investigation and Analysis of Routine Chemistry in China. Issue 5 (30th September 2015) - Fei, Yang; Wang, Wei; He, Falin; Zhong, Kun; Wang, Zhiguo
Abstract : Background: This study aims to investigate the imprecision of internal quality control of routine chemistry analytes so that we can have an overall knowledge of imprecision level of measurement in laboratories in China. Methods: The internal quality control information including two kinds of coefficient of variations (CVs) of 22 analytes were collected via an on‐line questionnaire. Then, the percentages of laboratories meeting the quality requirement for each analyte were calculated according to five imprecision criteria. Results: Among these 22 analytes, creatine kinase got the most satisfied result, the percentages of laboratories whose current CV met 1/3 total allowable error (1/3TEa), 1/4TEa, and the specifications based on biological variation were 99.3%, 95.9%, 99.6%, 99.9%, and 90.6%, respectively, while Na got the lowest satisfaction rate according to these specifications, which were 4.15%, 22.4%, 4.2%, 9.0%, and 1.3%, respectively. From an overall perspective, most of the 22 analytes got a satisfied result when applying the criteria defined by CLIA'88, while only a small amount of laboratories can meet the requirement when applying the specifications derived from biological variation. Conclusions: There is huge space for us to enhance and substantial effort is needed in improving and implementing quality management in China.